DAMPAK REPATRIASI BAGI PARA EKSPATRIAT NEGARA - Rimayanti Rimayanti (Fakultas Syariah UIN Antasari, 2019)
AbstractAlong with the development of business by multinational companies, the role of expatriates is increasing rapidly. But these expatriates face problems that are not easy when the assignment period ends and they return to their home countries. The various problems found were motivated by work-related factors, as well as social factors. Based on the explanation of this problem, several strategies that must be carried out by the company in overcoming the impact of repatriation, for example, provide 6 months of training before returning or provide assistance to overcome cultural shock after the assignment period is over and expatriates return to their respective countries. Keywords: Repatriation, Expatriate, Strategy, Multinationals. AbstrakSeiring dengan perkembangan bisnis oleh perusahaan multinasional, peran para ekspatriat meningkat dengan pesat. Namun para ekspatriat ini menghadapi masalah yang tidak mudah saat masa penugasan berakhir dan mereka pulang kembali ke negara asal. Beragam masalah yang dijumpai ternyata dilatarbelakangi oleh faktor- faktor yang berhubungan dengan pekerjaan, dan juga faktor- faktor sosial. Berdasarkan pemaparan dari permasalahan ini, beberapa strategi yang harus dilakukan oleh pihak perusahaan dalam mengatasi dampak repatriasi ini misalnya memberikan training 6 bulan sebelum kepulangan ataupun menyediakan pendampingan guna mengatasi gegar budaya setelah masa penugasan usai dan para ekspatriat kembali ke negaranya masing- masing. Kata Kunci: Repatriasi, Ekspatriat, Strategi, Multinasional.